International Monitoring Station:National Interest Perspective-Technological Point of View - Perpustakaan UGM, i-lib ([Yogyakarta] : Fakultas Ekonomi,UGM, 1997)
, "The ratification of Comprehensive Test Ban Treaty (CTBT) by most of member states of the United Nations (UN) Organization proves that nuclear weapons must be eliminated worldwide. Since some countries that own nuclear weapons still do, not comply with regulations, it is necessary for the UN to take action in monitoring their activities. This manuscript describes the method to conduct monitoring using radiological background information and seismic events. Combination of both information and the use of Artificial Intelligence approach should be able to provide decision about monitoring data accurately.